pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.570
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cell Proliferation and Cell Death in Human Follicle Dermal Papilla Cells by Zinc Chloride

Abstract: Tsai et al.: Zinc Induces Cell Proliferation and Cell Death in HFDPCs In the present investigation, the effects of zinc on the growth of human follicle dermal papilla cells were determined. A higher dose of zinc was found to significantly increase the proliferation of human follicle dermal papilla cells and the expression levels of cell cycle regulatory proteins. However, cell death, an increase in the apoptotic protein Bax, and caspase-3 activation were also observed in zinc-treated human follicle dermal papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…An increase in the apoptotic Bax protein and caspase-3 activation were observed. The results of this study suggest that zinc is involved in the regulation of proliferation or death of human dermal papilla cells in the follicle, but in a narrow dose range [33]. The fact that Zn plasma levels in the positive effect and absence of effect groups were equal upon completion of conservative treatment most likely indicates the prognostic significance of the initial Zn plasma level in relation to the effectiveness of conservative therapy, but not a decisive role in realizing the positive effect of treatment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…An increase in the apoptotic Bax protein and caspase-3 activation were observed. The results of this study suggest that zinc is involved in the regulation of proliferation or death of human dermal papilla cells in the follicle, but in a narrow dose range [33]. The fact that Zn plasma levels in the positive effect and absence of effect groups were equal upon completion of conservative treatment most likely indicates the prognostic significance of the initial Zn plasma level in relation to the effectiveness of conservative therapy, but not a decisive role in realizing the positive effect of treatment.…”
Section: Discussionmentioning
confidence: 78%
“…At the same time, the concentration dependence of zinc on the proliferation of the dermal papilla cells of a human follicle and the expression of regulatory proteins of the cell cycle have also been demonstrated. Tsai et al reported that zinc chloride at a dose of 200-500 nmol significantly increases the proliferation of human follicle dermal papilla cells and the expression of cell cycle regulatory proteins [33]. However, the production of proteins associated with the cell cycle has decreased when the cells were treated with 1000 nmol zinc chloride.…”
Section: Discussionmentioning
confidence: 99%